Development of Pascal's Law Learning Media Using Augmented Reality Based on the Marker Based Tracking - Mugi Sukmawati; Muhammad Nasir (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The advancement of educational media has continued to evolve in parallel with technological progress. One of the emerging technologies applicable to learning environments is Augmented Reality (AR). The integration of AR in instructional media provides an engaging and interactive learning experience that supports students’ comprehension, particularly in understanding complex physics concepts such as Pascal’s Law. This study aims to develop an Android-based learning medium utilizing Augmented Reality to facilitate the teaching and learning of Pascal’s Law. The research employed a development approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were analyzed using descriptive analysis techniques. The developed media was evaluated by design experts, content experts, pedagogical experts, and technical experts, as well as tested on 28 students from SMA N 1 Logas Tanah Darat, Kuantan Singingi Regency, Riau Province. The validation results indicated a validity score of 0.903, categorized as very valid, and a practicality score of 90.08, categorized as very practical. These findings suggest that the Augmented Reality based learning media developed for Pascal’s Law is both valid and practical for use in classroom learning to enhance students’ conceptual understanding.Keywords: the ADDIE model, augmented reality, pascal's law, learning media